2019
DOI: 10.1002/jcb.28908
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antibacterial activity of Zataria multiflora Boiss extract and its components, carvacrol, and thymol, against colistin‐resistant Acinetobacter baumannii in a pneumonic BALB/c mouse model

Abstract: Background Acinetobacter baumannii has emerged as a major cause of nosocomial infections. Various resistance mechanisms of A. baumannii against antibiotics have transformed it into a successful nosocomial pathogen. Because of the limited number of available antibiotics, we used a medicinal plant with an antibacterial effect. Zataria multiflora Boiss (ZMB) extract and its components were used for the treatment of pneumonic mice infected with A. baumannii. The biological effects of this extract and the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Twenty-one monoterpenoids were reported in our Review, among which ten exhibited high in vitro antibacterial activity. All of them were found in EOs from plants and have received much attention for their significant antibacterial activity, with four compounds (α-terpineol, carvacrol, eucalyptol, and thymol) being investigated with in vivo models of bacterial infections, , and six (α-pinene, carvacrol, eucalyptol, linalool, terpinen-4-ol, and thymol) tested in clinical trials (Table ) related to infectious and inflammatory conditions (e.g., gingivitis, sore throat, episiotomy, acute bronchitis, blepharitis). ,, Although highly active, these compounds present some drawbacks reducing their use as antibacterial agents, especially their unfavorable physicochemical profile with high volatility leading to instability and a short half-life, a low water solubility leading to a poor bioavailability after oral administration, an unpleasant taste and smell, and potential toxicity due to poor knowledge concerning the optimal safe dose to be administered. Future research directions include improvement of physicochemical properties, the examination of acute and chronic toxicity as well as teratogenicity, development of standardized formulations with multiple compounds, and realization of clinical trials focused on multidrug resistant bacterial infections.…”
Section: Plant-derived Compounds With Antibacterial Propertiesmentioning
confidence: 99%
“…Twenty-one monoterpenoids were reported in our Review, among which ten exhibited high in vitro antibacterial activity. All of them were found in EOs from plants and have received much attention for their significant antibacterial activity, with four compounds (α-terpineol, carvacrol, eucalyptol, and thymol) being investigated with in vivo models of bacterial infections, , and six (α-pinene, carvacrol, eucalyptol, linalool, terpinen-4-ol, and thymol) tested in clinical trials (Table ) related to infectious and inflammatory conditions (e.g., gingivitis, sore throat, episiotomy, acute bronchitis, blepharitis). ,, Although highly active, these compounds present some drawbacks reducing their use as antibacterial agents, especially their unfavorable physicochemical profile with high volatility leading to instability and a short half-life, a low water solubility leading to a poor bioavailability after oral administration, an unpleasant taste and smell, and potential toxicity due to poor knowledge concerning the optimal safe dose to be administered. Future research directions include improvement of physicochemical properties, the examination of acute and chronic toxicity as well as teratogenicity, development of standardized formulations with multiple compounds, and realization of clinical trials focused on multidrug resistant bacterial infections.…”
Section: Plant-derived Compounds With Antibacterial Propertiesmentioning
confidence: 99%
“…The use of natural compounds has been suggested to be a safe and effective therapeutic option to fight against drug-resistant A. baumannii ( Tsai et al, 2018 , Hassannejad et al, 2019 ). Natural compounds such as thymol and carvacrol showed antibacterial effects against drug-resistant A. baumannii ( Hassannejad et al, 2019 ). In another study, Tsai reported the activity of Scutellaria barbata against A. baumannii ( Tsai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the antimicrobial importance of these compounds, since they were able to maintain broad-spectrum, noteworthy antimicrobial activity across all the strains tested. Previous studies have also reported on the antimicrobial activities of carvacrol, cinnamaldehyde, isoeugenol, and thymol against several of the pathogens [35][36][37][38][39][40][41][42][43][44][45][46]. Phenolic compounds (carvacrol and thymol) could be…”
Section: Introductionmentioning
confidence: 99%